(untitled) - Ashby, Robert (Boston, 2005)
This it the first technical reference book available on the PSoC, and it offers the most comprehensive combination of technical data, example code, and descriptive prose you'll find anywhere.
Keywords: Systems on a chip,Hệ thống trên vi mạch; Design and construction,Thiết kế và cấu trúc